Digital Self-Enslavement: The Implications of the Internet of Things for Cyber Law Reform in the Society 5.0 Era within the Framework of Maqashid al-Sharia - Lbn Batu, Dewi Pika; Siahaan, Parlaungan Gabriel; Taufiq Ramadhan; Pinem, Windawati; Maulana Ibrahim; Sitorus, Gita Oktaviani (Institut Agama Islam Negeri Kendari, 2026)
This study investigates the emerging phenomenon of